USE OF MEDIA STIMULATION OF BEAM HOUSING TO INCREASE CHILDREN'S EMOTIONAL SOCIAL EMOTIONALITY - Yusrina, Neng Dewi (EMPOWERMENT : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
ABSTRACTEarly childhood has several aspects of development that need to be improved. Developing children's emotional social influenced by stimuli from the surrounding environment, through teacher school environments can facilitate and provide stimulation to develop children's emotional social optimally. To be able to interact with the surrounding environment, emotional social ability is an initial ability that must be owned by the child. For children to interact with their wider environment. The learningprocess conducted in Kartina Kindergarten Garut Regency to improve the emotional social intelligence of early childhood using the media stimulation of the beam house. This is because the emotional social aspect of children still needs to be improved.This study focuses on the use of home media blocks to improve children's emotional social intelligence. This research was conducted by using qualitative approach of case study method. Data collection techniques used are observation, interview, and documentation. With the subject of the study of students B1 grade 5-6 years of age, teachers and parents.The results obtained from this study show that: (1) the learning process in Katrina Kindergarten Garut Regency has basically been taken through the stages of programmed and systematic planning in the form of RKH (Daily Activity Plan) that produce teaching materials and media used to be an implemented teacher; (2) The use of house block beam stimulation media in children aged 5-6 years in Kartina Kindergarten Tarogong Kidul District Garut Regency quite effective in improving emotional social intelligence;(3) increased emotional social intelligence of children in realizing the development of the child in terms of empathy (sensitivity to the feelings of others); express feelings, restrain anger; independent; can adapt; able to solve personal problems; perseverance; solidarity; courtesy; and respect. Keywords: Media Stimulation Home Beam, Emotional Social Intelligence, Early Childhood